2019
DOI: 10.1097/j.pain.0000000000001514
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the genetic architecture of back pain and its risk factors from a study of 509,000 individuals

Abstract: Back pain (BP) is a common condition of major social importance and poorly understood pathogenesis. Combining data from the UK Biobank and CHARGE consortium cohorts allowed us to perform a very large GWAS (total N = 509,070) and examine the genetic correlation and pleiotropy between BP and its clinical and psychosocial risk factors. We identified and replicated three BP associated loci, including one novel region implicating SPOCK2/CHST3 genes. We provide evidence for pleiotropic effects of genetic factors und… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
126
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(150 citation statements)
references
References 80 publications
(62 reference statements)
24
126
0
Order By: Relevance
“…Slc39a8 mutant zebrafish exhibit vertebral abnormalities, impaired growth, and decreased motor activity, and a missense GIP1-associated polymorphism rs13107325 in the SLC39A8 gene has previously been associated with the increased risk of osteoarthritis 54 and severe adolescent idiopathic scoliosis 57 . Thus, similar to findings from our recent study of back pain 45 , genetic factors underlying chronic musculoskeletal pain comprise biological, social, and psychological components.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Slc39a8 mutant zebrafish exhibit vertebral abnormalities, impaired growth, and decreased motor activity, and a missense GIP1-associated polymorphism rs13107325 in the SLC39A8 gene has previously been associated with the increased risk of osteoarthritis 54 and severe adolescent idiopathic scoliosis 57 . Thus, similar to findings from our recent study of back pain 45 , genetic factors underlying chronic musculoskeletal pain comprise biological, social, and psychological components.…”
Section: Discussionsupporting
confidence: 85%
“…Traits that displayed the strongest genetic correlations with GIP1 were osteoarthritis (rg = 0.65), age of first birth (rg = −0.56), depressive symptoms (rg = 0.54), and college completion (rg = 0.54). Overall, the pattern of genetic correlations with GIP1 was very similar to that observed for back pain in our previous study 45 . GIP2 was genetically correlated only with osteoarthritis (inverse genetic correlation, rg = −0.30) and obesity-related traits, and GIP4 only with hip circumference ( Supplementary Data 11b, c).…”
Section: Articlesupporting
confidence: 86%
“…Using Complex Traits Genetics Virtual Lab (CTG-VL) [18], we explored whether those SNPs have been previously associated to other traits. We observed that rs10660361 was also identified by a recent GWAS on back pain (P-value = 7.77×10 −8 ) [25] and multisite chronic pain (P-value = 1.9×10 −9 ) [36]. However, rs113313884 was only associated with multisite chronic pain at a suggestive level (P-value = 6.9×10 −3 ) highlighting the importance of studying phenotypes using different definitions.…”
Section: Resultsmentioning
confidence: 74%
“…Evidence for the role of genetic factors in CP comes from twin and family studies [38] where its heritability is estimated to be as high as 60% [11,37]. More recently, large-scale genome-wide association studies (GWAS) have identified multiple genetic variants associated with chronic back pain [25,75] and multisite chronic pain [36] as further evidence of a genetic contribution to CP. However, their causal relationship has yet to be adequately examined.…”
Section: Introductionmentioning
confidence: 99%
“…The development of high‐throughput genotyping technologies and large biobank collections, complemented with rapid methodological advances in statistical genetics, has enabled hypothesis‐free genome‐wide association studies (GWAS), which have identified hundreds of genetic variants across many loci associated with musculoskeletal conditions such as fracture, ( 7,8 ) osteoarthritis, ( 9 ) and sarcopenia, and their related endophenotypes including bone mineral density, ( 10–13 ) lean mass, ( 14 ) grip strength ( 15,16 ) and even back pain. ( 17 ) As large‐scale whole‐genome (WGS) and exome sequencing data become available, even more variants will be identified. ( 18 ) These studies provide a fertile ground for understanding the biologic pathways underlying the genetic architecture of musculoskeletal traits.…”
Section: Introductionmentioning
confidence: 99%